1958
DOI: 10.1175/1520-0477-39.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Large Convective Rainstorms in Relation to Winds Aloft

Abstract: By means of hourly rainfall data from the Hydroclimatic Network, the motions of large rainstorms, of the kind associated with squall lines, are examined in relation to the winds aloft. Very little correlation is found between the speed of movement of the rainstorms and the wind speed at any level, although the fastest moving storms were associated with strong winds aloft. Significant correlation is found between direction of motion of rainstorms, and wind direction at 700 mb or higher levels. On the average, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

1962
1962
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 7 publications
3
12
0
2
Order By: Relevance
“…The development and progression of the storm corresponds well with the observations of similar multicellular convective storms reported by authors such as Browning and Ludlam (1962), Newton and Katz (1958), and Newton and Fankhauser (1975). The propagation and development of severe local storms is discussed by Sumner (1988).…”
Section: Storm Dynamicssupporting
confidence: 86%
“…The development and progression of the storm corresponds well with the observations of similar multicellular convective storms reported by authors such as Browning and Ludlam (1962), Newton and Katz (1958), and Newton and Fankhauser (1975). The propagation and development of severe local storms is discussed by Sumner (1988).…”
Section: Storm Dynamicssupporting
confidence: 86%
“…Chappell () noted that most flash floods are produced by quasi‐stationary precipitation systems, wherein many convective cells reach maturity and produce their heaviest rainfall over the same area. Newton and Katz () and Chappell () showed that a convective system's motion can be identified as being the vector sum of an advective component approximated by the mean cloud‐layer wind (direction and magnitude) and a propagation component governed by the rate and location of new cell formation relative to existing convection. Based on this idea, a vector‐based forecast technique was developed for predicting the motion of upwind‐ and downwind‐propagating mesoscale convective systems (MCSs; Corfidi, ; Corfidi et al, ).…”
Section: Analysis Of Key Factors For the Heavy Rainfallmentioning
confidence: 99%
“…Chappell (1986) noted that most flash floods are produced by quasi-stationary precipitation systems, wherein many convective cells reach maturity and produce their heaviest rainfall over the same area. Newton and Katz (1958) and Chappell (1986) showed that a convective…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Apesar dessa ressalva, os resultados obtidos neste trabalho vão ao encontro daqueles encontrados por diversos autores (Velasco & Fritsch, 1987;Machado et al, 1998;Siqueira, 2004;Vila, 2004;Durkee & Mote, 2009;Sakamoto, 2009;Sakamoto et al, 2009, por exemplo), que mostraram que os SCM subtropicais sul-americanos tendem a se deslocar para leste desde sua gênese até sua dissipação. Isso ocorre porque o movimento do SCMé a soma de uma componente advectiva, dada pelo deslocamento médio das células convectivas, e uma componente de propagação, definida pela taxa de formação e localização de novas células (Newton & Katz, 1958;Newton & Newton, 1959;Bluestein & Jain, 1985). Quantoàs células convectivas individuais imersas nos SCM, estas tendem a se mover a favor do fluxo médio na camada de nuvens.…”
Section: Horários Mais Frequentes De Iniciações Maturações E Dissunclassified